ADULT MATHEMATICAL LITERACY SISWA BERDASARKAN AKTIVITAS LITERASI MATEMATIS - Nurcholif Diah Sri Lestari; Wasilatul Murtafiah; Fitri Annisa; Maharani Hayuning P. P; Marheny Lukita Sari (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
Adult mathematical literacy of high school students rarely gets attention, even though they need this skill to face various life challenges and situations. This research aims to describe the adult mathematical literacy based on activities of mathematical literacy’s processes domain when solving problems. Therefore, three high school students with equivalent mathematical abilities in specialization mathematics and compulsory mathematics are selected as research subjects. Data collection are through tests and interviews. The Data reduced, triangulated using the triangulation method, presented, and used in concluding. The results indicate that high school students with high mathematical abilities can use the ability to formulate situations mathematically, using concept facts, procedures, and mathematical reasoning; and interpret mathematical solutions. However, in formulating the situation, they tend only to identify aspects or components whose value is known by using familiar symbols. They also tend to make mistakes in making mathematical reasoning, especially if the problem involves reasoning with many criteria and conditions, as well as errors in interpreting solutions that contain limitations or constraints. The results suggested to familiarize students with everyday problems that involve reasoning to help students recognize problem situations as mathematical situations and generate creativity in using mathematical knowledge